PENGARUH KONSUMSI JUS KACANG HIJAU (PHASEOLUS RADIATUS) TERHADAP HEMOGLOBIN IBU HAMIL ANEMIA DI PUSKESMAS TJ. PASIR KEC.KUALUH SELATAN KAB. LABUHAN BATU UTARA TAHUN 2020 - Septa Dwi Insani; Eka Sri Wahyuni; Dewi Wahyuni (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Anemia is the biggest public health problem in the world, especially for women of childbearing age and is a major nutritional problem in Indonesia. One of the risks of iron deficiency anemia can lead to increased body weight of low pregnant women and premature birth of babies. This study aims to determine the effect of giving mung beans to hemoglobin levels in pregnant women with mild anemia in trimester III at May Resti, Amd. Keb Maternity Clinic Dangung-Dangung. This type of research is a Quasi Experiment with a one-group pre-test post-test design. The analysis used was univariate and bivariate analysis. The sample selection used a purposive sampling technique as many as 16 pregnant women with mild anemia. Each respondent was given treatment by giving green bean juice as much as 250 cc, 2 times a day for 7 days. Measurement of hemoglobin levels was carried out 2 times, namely 1 day before and on the 9th day after consumption of green bean juice. There is an effect of green beans on the increase in hemoglobin levels of pregnant women but it is not too significant. For preventive efforts in preventing anemia, pregnant women should consume this green bean juice. In this study, we obtained suggestions to promote green bean juice in an effort to prevent anemia in pregnant women.